Attitudes and preferences in patients with acromegaly on long-term treatment with somatostatin analogues - Cecilia Follin; Sven Karlsson (Endocrine Connections, 2016)
Introduction: Patients with acromegaly can be treated with surgery, medical therapy and/or radiation therapy. For the patients not being cured with surgery, treatment with somatostatin analogues (SSAs) is the primary therapy. SSA can be taken by self- or partner-administered injections in addition to being given by a nurse at a clinic. The aim was to assess if patients with acromegaly prefer self-injections and to investigate their attitudes towards long-term medical therapy. Method: All patients in the southern medical region of Sweden with a diagnosis of acromegaly and treated with SSA were eligible for the study (n = 24). The study is based on a questionnaire asking about the patients’ attitudes and preferences for injections with SSA, including their attitudes towards self-injection with SSA. Results: The patients’ (23 included) median age was 68.5 years and the patients had been treated with SSA for 13 (1–38) years. One patient was currently self-injecting. All of the other patients were receiving injections from a nurse at a clinic. Three patients preferred self-injections, one preferred partner injections and 19 patients did not prefer self- or partner injections. The most frequent arguments to not preferring self-injections were ‘feeling more secure with an educated nurse’ and ‘preferring regular contact with a specialised nurse’. Conclusion: Patients with acromegaly prefer regular contact with the endocrine team to the independence offered by self-injections. These findings might mirror the patients’ desires for continuity and safety. We need to address patients’ concerns regarding injections with SSA and support them in their choices.